Effect of amino acids as growth stimulant for recovery of Shigella spp. - Alam, Ashfaqul; Ara, Lutfe; Begum, Anowara; Khan, Sirajul Islam (Dhaka University Journal of Biological Sciences, 2011)
Key words: Response; Amino acid; Shigella spp.; Enrichment DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8981 DUJBS 2011; 20(2): 201-204